Manufacturing method of Al-Ti-C grain refiner applied to high-toughness aluminum alloy

Through batch feeding process and material ratio design, the poor wetting and uneven tissue problems of Al-Ti-C grain refiner in aluminum alloys are solved, and high purity and uniform distribution of Al is achieved -Ti-C refining agent improves the fracture toughness of aluminum alloy and is suitable for aviation aluminum alloy materials.

CN119287202APending Publication Date: 2025-01-10HEBEI SITONG NEW METAL MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411406216.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the application of existing Al-Ti-C grain refining agents in aluminum alloys, there are problems such as poor wetting properties of carbon and aluminum, excessive slag inclusions, uneven tissues, and unstable application performance, making it difficult to achieve industrial production and widespread application. .

Method used

Using batch-sequential feeding process, potassium fluorotitanate, titanium powder, carbon powder and auxiliary materials K3AlF6 or Na3AlF6 are uniformly mixed. The feeding temperature and speed are controlled by heating and melting in an induction furnace to form a uniform distribution of TiAl3 and TiC phases, and the reaction is removed. The products and scum are degassed and refined, and finally cast or rolled into high-purity Al-Ti-C grain refining agent.

Benefits of technology

The composition uniformity and structure uniformity of the Al-Ti-C grain refining agent are achieved, the refinement performance is improved, the fracture toughness of aluminum alloy is enhanced, and the industrialization needs of aviation aluminum alloy materials are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287202A_ABST
    Figure CN119287202A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing method of an Al-Ti-C grain refiner applied to a high-strength and high-toughness aluminum alloy, which is characterized in that raw materials are added in two times, the first batch is a titanium (Ti)-containing material or a part of titanium-containing material and a part of carbon (C)-containing material; the second batch is the remaining titanium-containing material and carbon-containing material. The titanium-containing material is potassium fluotitanate and titanium powder. According to the invention, through material selection, proportioning, charging and process design, the problems of wetting and alloying of carbon in aluminum are solved, the generated TiAl3 and TiC phases are fine, dispersed and high in purity and have good refining capacity, and the fracture toughness of the high-strength and high-toughness aluminum alloy is improved after the TiAl3 and TiC phases are added.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials and relates to an aluminum alloy material, in particular to a method for manufacturing an Al-Ti-C grain refiner for producing aviation high-strength and tough aluminum alloy materials. Background Art

[0002] With the trend of lightweight parts in high-speed rail, aerospace and special application fields, the requirements for the comprehensive performance of aluminum alloy materials are getting higher and higher, pushing aluminum alloy materials to develop in the direction of finer and more uniform organization. The key to obtaining a fine and uniform aluminum alloy is how to achieve a fine and uniform grain structure, that is, the refinement of the alloy. The method widely used in industrial production at present is to add a grain refiner to the melt. Al-Ti-B master alloy is a relatively mature grain refiner, but Al-Ti-B (aluminum-titanium-boron) master alloy has its own defects that are difficult to overcome. With the further research on grain refiners, Al-Ti-C (aluminum-titanium-carbon) grain refiners have entered the field of vision of material researchers. Al-Ti-C grain refiners can improve the "poisoning" and refinement decay problems of Al-Ti-B, so the current research at home and abroad focuses on the research and development of Al-Ti-C grain refiners.

[0003] Cibula et al. proposed the "carbide" theory in the 1950s, that is, the TiC phase particles formed by the alloy element Ti and the trace element C in the alloy melt are the heterogeneous cores of α-Al crystallization. In order to introduce a sufficient amount of C into the aluminum melt, Cibula added graphite powder, graphite rods, or passed CC14, CO and C2H2 into the aluminum melt, but due to the extremely poor wettability of C element to Al liquid, it was difficult for C to enter the Al-Ti alloy melt. It was not until 1986 that Banerji et al. successfully synthesized the Al-Ti-C intermediate alloy containing a large number of TiC particles in the Al-Ti alloy using a special process. In the 1980s, companies such as KBA in the United States and AB in the United Kingdom began to study a new generation of Al-Ti-C grain refiners. The characteristics of their research were that the mass fraction of carbon was very low or the ratio of Ti:C was very high. In the 1990s, the British LSM and SMC companies developed a new Al-Ti-C grain refiner to meet the needs of high-performance aluminum alloy materials for pollution-free and efficient grain refiners, and it has been recognized by manufacturers. Studies have shown that compared with Al-Ti-B grain refiners, the TiC nucleation particles in the Al-Ti-C refiner will not have a "poisoning" effect on certain aluminum alloys containing Zr elements, thereby improving the comprehensive performance of aluminum alloy materials. Aluminum-titanium-carbon (Al-Ti-C) refiner is an important additive material in the production and manufacturing of 7XXX series (Al-Zn-Mg-Cu) high-strength civil aviation aluminum materials. It can improve the comprehensive properties of the material such as fracture toughness and play an important role in improving the performance of aviation materials.

[0004] The research on grain refiners in China started late, and the research on Al-Ti-C grain refiners began in the 1980s. Due to the poor wettability of aluminum melt and C, the interface reaction is slow and difficult to alloy. At the same time, due to the poor stability and accuracy of traditional production methods, the generation of effective refined particles cannot be guaranteed, resulting in the loss of product refinement ability. At present, Al-Ti-C grain refiners have not been widely produced and applied in industry.

[0005] CN102634764A discloses a method for manufacturing an enhanced aluminum-titanium-carbon alloy wire, which uses a TiC reinforcement to add to an aluminum melt, and prepares an enhanced aluminum-titanium-carbon alloy wire through atomization, solidification, and cold drawing annealing. However, the raw material TiC of this technology has poor wettability with aluminum liquid, and the preparation temperature is high, the process is complicated, and the production equipment is required to be high, making it difficult to achieve industrial production. CN104894417A discloses an aluminum-titanium-carbon intermediate alloy refiner and preparation process. The patent uses a certain grade of aluminum alloy (a certain grade of recycled waste aluminum), potassium fluorotitanate, potassium fluoroborate, and a carbon source as raw materials to make a mixed batch, which is added to aluminum water at 700 to 900°C at one time, and is stirred, left to stand, slag-scraped, refined, and formed into an ingot or wire. The carbon source of this method needs to be ball-milled into powder, which has a complicated process, a long process, and increases costs. Moreover, the feeding temperature is low, and it is difficult to ensure the full reaction of the carbon powder, which may result in poor product microstructure and unstable refinement performance. Summary of the invention

[0006] The purpose of the present invention is to overcome the quality deficiencies of existing products, with the key being to improve the microstructure of the product, thereby improving the refining ability, thereby providing a method for manufacturing an Al-Ti-C grain refiner for high-strength and tough aluminum alloys, solving the problems of poor wettability of carbon and aluminum liquid, formation of many slag inclusions, uneven organization, and unstable application performance. The Al-Ti-C grain refiner manufactured has uniform composition and organization, dispersed distribution of TiAl3 and TiC phases in the microstructure, high alloy purity, and good refining ability, meeting the needs of industrial use in the field of aluminum and aluminum alloy material manufacturing.

[0007] The technical solution to solve the problem of the present invention is:

[0008] The present invention provides a method for manufacturing an Al-Ti-C grain refiner for high-strength and toughness aluminum alloy, comprising the following steps:

[0009] S1 adds the aluminum ingot into the induction furnace, heats and melts it, degasses it for 10 to 30 minutes at a temperature of 700 to 750°C, and then removes the slag;

[0010] S2: heating the aluminum melt to 700-900°C, mixing the first batch of raw materials evenly, adding them at a uniform speed using a feeding car, stirring the melt continuously during feeding, controlling the feeding time to 5-30 minutes, keeping the alloy at 800-900°C for 5-20 minutes, and removing the reaction product or ash; transferring the alloy melt to another electric furnace or continuing to heat it to 1000-1300°C, mixing the second batch of raw materials evenly, pressing them into blocks, adding the alloy melt continuously or in 2-3 times at a uniform speed, stirring the melt continuously during feeding, stirring the melt for 5-15 minutes after each feeding, controlling the temperature at 1000-1350°C, and controlling the total feeding time to 20-90 minutes. After the feeding is completed, alloying is kept at 1000-1350°C for 10-60 minutes;

[0011] The first batch of raw materials is partly titanium-containing material or partly titanium-containing material and partly carbon-containing material;

[0012] The second batch of raw materials is the remaining titanium-containing material and carbon-containing material;

[0013] S3 slag removal: after the reaction is completed, clean the salt solution or surface oxides, and control the temperature at 800-1000℃;

[0014] S4 degassing and refining, the temperature is between 800 and 1000 ° C, and the alloy melt is degassed and refined for 10 to 60 minutes using argon gas to remove slag;

[0015] S5 casting and continuous casting and rolling, cleaning the slag on the surface of the melt, controlling the casting temperature at 800-1000°C, casting into ingots or rolling into wires, and the obtained aluminum-titanium-carbon grain refiner contains 2%-8wt% Ti and 0.05%-2.0wt% C.

[0016] Furthermore, auxiliary materials are added to the first batch of raw materials and / or the second batch of raw materials. The auxiliary materials are one or more of K3AlF6 or Na3AlF6, KCl or MgCl2, and the amount of the auxiliary materials added is 1 to 15% of the mass of the batch of raw materials.

[0017] Furthermore, the first batch of raw materials is mixed evenly and added in powder form at a uniform speed, and the second batch of raw materials is first mixed evenly and then packed tightly with aluminum foil or pressed into blocks of 10 to 1000 g. The two batches of materials are added separately, and each batch of materials is added once or multiple times.

[0018] Furthermore, the titanium-containing material is potassium fluorotitanate and titanium powder, the titanium powder is sponge titanium powder or metal titanium powder; the carbon-containing material is graphite powder or nano-carbon powder.

[0019] Furthermore, in the first batch of raw materials, the titanium content generated by potassium fluorotitanate accounts for 20% to 80% of the titanium content in the target alloy, the titanium powder content accounts for 1 to 10% of the Ti content in the target alloy, and the carbon powder content accounts for 5 to 40% of the carbon content in the target alloy; in the second batch of raw materials, the titanium content generated by potassium fluorotitanate accounts for 1% to 20% of the titanium content in the target alloy, the titanium powder content accounts for 10 to 50% of the Ti content in the target alloy, and the carbon powder content accounts for 50 to 95% of the carbon content in the target alloy.

[0020] Furthermore, the C component of the carbon-containing material is greater than 99%, the maximum particle size is less than 100 μm, the particle size of the titanium powder is less than or equal to 0.5 mm, and the purity is about 95%.

[0021] The key to the present invention lies in the selection and formulation design of materials, as well as the matching feeding process control, including grouping and formulating potassium fluorotitanate, titanium powder, carbon powder and salt auxiliary materials that meet the standards, uniformly mixing them in a certain proportion, and dividing them into two batches. The first batch of mixed materials are uniformly mixed in powder form, and then added at a uniform speed, mainly at a lower temperature to form a part of particles; the second batch of materials are uniformly mixed and pressed into blocks and added, and the material particles are pressed into blocks according to proportion, added at a higher temperature, added to the melt and combined with the tissue formed by the first batch of materials, and potassium fluorotitanate is beneficial to increase the reaction of carbon and aluminum; industrial pure aluminum is added to an induction furnace and heated to completely melt and heated to a certain temperature, and then the mixed materials are added in batches in sequence, and the feeding temperature and speed are strictly controlled. After sufficient reaction and alloying, the reaction products and scum are removed, and degassing and refining are carried out to obtain a pure alloy; finally, it is cast into ingots or continuously rolled into wires. The present invention focuses on achieving uniform composition, high purity, uniform particle dispersion and good refining ability of Al-Ti-C refiner through raw material ratio design, mixing, feeding design and process control. Typical alloy grades mainly include AlTi3C0.15, AlTi5C0.2, AlTi3C0.3, AlTi5C0.5, etc. Adding to 7XXX series aluminum alloy can improve the fracture toughness of aluminum alloy.

[0022] The present invention utilizes potassium fluorotitanate to react with aluminum to generate a protective layer, thereby reducing the burning loss during the alloying reaction process; utilizes the particle size matching and component ratio matching of sponge titanium powder, metal titanium powder and graphite powder to control the formation of effective particles in the reaction process; utilizes the addition of auxiliary materials such as K3AlF6 or Na3AlF6, KCl or MgCl2 to facilitate the separation of slag inclusions during the reaction process, improve the wettability of carbon powder and aluminum liquid, and improve the purity of the melt; utilizes the ratio design of two groups of materials and the sequential feeding control to form a uniform, dispersed structure and effective particles, thereby improving the refinement ability of the product.

[0023] Advantages and beneficial effects of the present invention:

[0024] The present invention controls the stable progress of the alloying reaction process by batch sequential feeding and process matching, which is beneficial to the generation, morphology and structure control of different particles in the melt. In particular, the two groups of materials are added at different temperatures to promote the formation of effective TiAl3 and TiC particles and dispersed distribution. Adding auxiliary materials to the materials is beneficial to the separation and removal of reaction products during alloying. The Al-Ti-C grain refiner manufactured by the technology of the present invention has uniform composition, low slag inclusion content, uniform TiAl3 phase size in the microstructure, fine and dispersed TiC phase, and excellent refinement performance. The second phase in the alloy microstructure is mainly TiAl3 particles and TiC particles.

[0025] The Al-Ti-C grain refiner of the present invention can improve the fracture toughness of 7XXX series high-strength aluminum alloys by about 10%, meeting the requirements of aviation aluminum alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a flow chart of the manufacturing method of the present invention;

[0027] Figure 2 This is a photo of the hollow coil of AlTi3C0.15 wire manufactured in Example 1;

[0028] Figure 3 The microstructure of AlTi3C0.15 manufactured in Example 1;

[0029] Figure 4 This is a detailed photo of AlTi3C0.15 manufactured in Example 1;

[0030] Figure 5 The microstructure of AlTi3C0.15 manufactured in Comparative Example 1;

[0031] Figure 6 The microstructure of AlTi5C0.2 manufactured in Example 2;

[0032] Figure 7 The microstructure of AlTi5C0.2 manufactured in Comparative Example 2;

[0033] Figure 8 This is the microstructure diagram of AlTi5C0.2 manufactured in comparative example 3. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0035] Example 1: Production of AlTi3C0.15 grain refiner

[0036] According to the composition of AlTi3C0.15, and the output of about 1000kg of finished products, the amount of aluminum used is 980kg, and the theoretical content of titanium and carbon is about 5% and 10% respectively. The raw materials are divided into two batches. The first batch of raw materials contains 100kg of potassium fluorotitanate (accounting for about 63.1% of the total titanium content in the alloy), 0.5kg of sponge titanium powder (accounting for about 1.53% of the total titanium content in the alloy), and 0.1kg of carbon powder (accounting for about 6% of the total carbon content in the alloy); the second batch of raw materials contains 9.5kg of sponge titanium powder (accounting for about 29.06% of the total titanium content in the alloy), 10kg of potassium fluorotitanate (accounting for about 6.31% of the total titanium content in the alloy), and 1.55kg of carbon powder (accounting for about 94% of the total carbon content in the alloy).

[0037] In the first batch of raw materials, 7 kg of K3AlF6 was added, and in the second batch of raw materials, 2 kg of MgCl2 was added. The first batch of materials were mixed evenly and loaded into the material truck. After the second batch of materials were mixed evenly, they were pressed into a single block with a weight of 100 g.

[0038] Weigh 980kg aluminum ingots, add them to the induction furnace for melting, remove the ash and slag on the surface of the aluminum liquid, degas for 20 minutes, and control the temperature at 705℃. Use the charging car to add the first batch of raw materials at a speed of 5kg / min, and use the electromagnetic stirring of the electric furnace. Adjust the temperature to 805℃ for alloying for 10 minutes, remove the reaction products or ash and slag; continue to heat up to 1000℃, add the second batch of raw materials to the alloy melt at a uniform speed twice, stir the melt continuously during the addition, stir the melt for 10 minutes after each addition, control the temperature at 1100℃, and control the total feeding time at 65min. After the addition is completed, alloy and keep at 1100℃ for 30 minutes. After the reaction is completed, clean the salt solution or surface oxides, and control the temperature at 1000℃. Then degas and refine at 950℃ for 40 minutes and remove the slag. At 900℃, alloy casting and continuous casting and rolling are carried out.

[0039] The hollow roll photo of the AlTi3C0.15 product obtained in Example 1 is as follows Figure 2 The diameter of the wire product is 9.5 mm. The composition of AlTi3C0.15 obtained in Example 1 is shown in Table 1. It can be seen that the composition of Ti and C in AlTi3C0.15 is close to the theoretical value. The microstructure analysis results are shown in Table 2. Its typical photos are shown in Figure 3 It can be seen that TiAl3 and TiC particles are dispersed, the maximum size of TiC is 5μm (the standard requires less than 15μm), the organization is uniform, and the total length of oxide and salt attachments is 465μm (the standard requires less than 1000μm), which meets the standard requirements.

[0040] It was verified by the TP-1 grain refinement standard test method. 0.25% Al-Ti-C alloy was added to 99.7% pure aluminum melt, kept at 725°C for 2 minutes, cast into a standard conical specimen, cooled by circulating water cooling, and then the line intercept method was used to detect the grain morphology and grain size of the cross-section of a specific part of the specimen. The general standard requires that the average grain size should be less than 230μm. Figure 4 This is a photo of the refinement results. It can be seen from the figure that the grain structure is equiaxed grains, the average grain size is 185μm, and the refinement effect is good.

[0041] Comparative Example 1: Production of AlTi3C0.15 Grain Refiner

[0042] The difference from Example 1 is that the weight and proportion of the raw materials are the same, but all the materials are mixed evenly at one time, and the feeding and alloying parameters are kept the same as those in Example 1 as much as possible.

[0043] Weigh 980kg aluminum ingots, add them to the induction furnace for melting, remove the ash and slag on the surface of the aluminum liquid, degas for 20 minutes, and control the temperature at 705℃. Use a charging car to add twice at a speed of 5kg / min. Use the electromagnetic stirring of the electric furnace when adding. The amount of each charge is 25kg (about 20% of the total amount). Keep the alloy at 805℃ for 10 minutes, and remove the reaction products or ash and slag; the alloy melt is transferred to another electric furnace, and the temperature is continued to rise to 1000℃. The second batch of raw materials is added to the alloy melt at a uniform speed. The melt is stirred continuously during the addition. After each addition, the melt is stirred for 10 minutes, and the temperature is controlled at 1100℃. The total time of the addition is controlled at 65 minutes. After the addition is completed, the alloy is kept at 1100℃ for 30 minutes. After the reaction is completed, the salt solution or surface oxides are cleaned and the temperature is controlled at 1000℃. Then degassing and refining are carried out at 950℃ for 40 minutes, and slag is removed. At 900℃, alloy casting and continuous casting and rolling are carried out.

[0044] The wire produced in Comparative Example 1 was analyzed. From Table 1, it can be seen that the AlTi3C0.15 produced in Comparative Example 1 has a significantly low Ti content and an unqualified C content, indicating that Ti and C are obviously burned. The microstructure test results are shown in Table 2, and a typical photo is shown in FIG. Figure 5 It can be seen that with the one-time mixing, there are obvious oxide and salt inclusions in the organization, the maximum size of a single TiC particle is 52 μm, and the refinement capacity is 305 μm. In general, the quality of AlTi3C0.15 manufactured in Comparative Example 1 is unqualified.

[0045] Example 2: Production of AlTi5C0.2 grain refiner

[0046] According to the composition ratio of AlTi5C0.2, and the output of about 1000kg of finished products, the amount of aluminum used is 960kg, and the theoretical content of titanium and carbon is about 5% and 10% respectively. The raw materials are divided into two groups. The first batch of raw materials contains 175kg of potassium fluorotitanate (accounting for about 66.7% of the total titanium content in the alloy), 5kg of sponge titanium powder (accounting for about 9.5% of the total titanium content in the alloy), and 0.2kg of carbon powder (accounting for about 9.1% of the total carbon content in the alloy); the second batch of raw materials contains 9.5kg of sponge titanium powder (accounting for about 18.1% of the total titanium content in the alloy), 15kg of potassium fluorotitanate (accounting for about 5.7% of the total titanium content in the alloy), and 2kg of carbon powder (accounting for about 90.9% of the total carbon content in the alloy).

[0047] In the first batch of raw materials, 10 kg of K3AlF6 was added, and in the second batch of raw materials, 3 kg of MgCl2 was added. Then the two groups of materials were mixed evenly, the first batch of materials was loaded into a material truck, and the second batch of materials was pressed into a single block with a weight of 100 g.

[0048] Weigh 980kg aluminum ingots for melting, remove ash and slag on the surface of aluminum liquid, degas for 20 minutes, and control the temperature at 700℃. Use a charging car to add the first batch of raw materials at a speed of 5kg / min, and use the electromagnetic stirring of the electric furnace. Adjust the temperature to 800℃ and keep the alloy for 20 minutes, remove the reaction products or ash and slag; transfer the alloy melt to another electric furnace, continue to heat it to 1010℃, add the second batch of raw materials to the alloy melt at a uniform speed twice, stir the melt continuously during the addition, stir the melt for 10 minutes after each addition, control the temperature at 1110℃, and control the total feeding time at 70 minutes. After the addition is completed, alloy and keep it at 1110℃ for 30 minutes. After the reaction is completed, clean the salt solution or surface oxides, and control the temperature at 1010℃. Then degas and refine at 900℃ for 40 minutes and remove the slag. At 900℃, alloy casting and continuous casting and rolling are carried out.

[0049] The AlTi5C0.2 wire manufactured in Example 2 was analyzed, and its composition is shown in Table 1, wherein the composition of Ti and C is close to the theoretical value and qualified. The microstructure test results are shown in Table 2, and its typical photos are shown in Table 2. Figure 6 As shown in the figure, it can be seen that TiAl3 and TiC particles are dispersed, the maximum size of TiC particles is 5μm, the structure is uniform, the total size of oxides and salt attachments is 540μm, and the refinement ability is 175μm.

[0050] Comparative Example 2: Production of AlTi5C0.2 Grain Refiner

[0051] The difference from Example 2 is that the materials are also added in two batches, but the proportion of titanium material in the first batch is different from that in Example 2. The process is the same, as follows:

[0052] According to the composition of AlTi5C0.2, the total feed is 1000kg, the amount of aluminum is 960kg, and the titanium and carbon are based on the theoretical content. In the first batch of raw materials, 50kg of potassium fluorotitanate (accounting for about 19% of the total titanium content in the alloy), 10kg of sponge titanium powder (accounting for about 19% of the total titanium content in the alloy), and 0.2kg of carbon powder (accounting for about 9.1% of the total carbon content in the alloy) are weighed; in the second batch of raw materials, 29.5kg of sponge titanium powder (accounting for about 56.3% of the total titanium content in the alloy), 15kg of potassium fluorotitanate (accounting for about 5.7% of the total titanium content in the alloy), and 2kg of carbon powder (accounting for about 90.9% of the total carbon content in the alloy) are weighed.

[0053] The weight ratio of the auxiliary materials added is the same as that in Example 2.

[0054] The parameters of the charging and alloying processes are the same.

[0055] The AlTi5C0.2 wire obtained in Comparative Example 2 was analyzed. Its composition is shown in Table 1. The Ti and C contents are low. The microstructure test results are shown in Table 2. The single size of TiC reaches 133 μm. Its typical photo is shown in Figure 7 The oxide and salt attachments shown are 4092 μm, and after the refinement ability test, the average grain size of 278 μm is unqualified.

[0056] Comparative Example 3

[0057] The difference from Example 2 is that no MgCl2 is added to the second batch of raw materials, and the other process operations are the same.

[0058] The AlTi5C0.2 obtained in Comparative Example 3 was analyzed. Its composition is shown in Table 1. The Ti and C contents are close to the theoretical ingredients. The microstructure test results are shown in Table 2. Its typical photos are shown in Table 2. Figure 8 The total length of the oxides and salt attachments shown is 4509μm. There are serious black strip-shaped oxides, the salt slag content is large, the slag-aluminum separation effect is poor, and the refinement effect of 235μm is unqualified.

[0059] Table 1 Al-Ti-C wire product composition and refinement effect

[0060]

[0061] Table 2 Microstructure of Al-Ti-C wire products (longitudinal section, any 1cm 2 )

[0062]

[0063] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. A method for producing an Al-Ti-C grain refiner for high-strength and tough aluminum alloy, characterized in that: The following steps are involved: S1 adds the aluminum ingot into the induction furnace, heats and melts it, degasses it for 10 to 30 minutes at a temperature of 700 to 750 degrees, and then removes the slag; S2: heating the aluminum melt to 700-900°C, mixing the first batch of raw materials evenly, adding them at a uniform speed using a feeding car, stirring the melt continuously during feeding, controlling the feeding time to 5-30 minutes, keeping the alloy at 800-900°C for 5-20 minutes, and removing the reaction product or ash; the alloy melt is transferred to another electric furnace or continues to heat to 1000-1300°C, briquetting the second batch of raw materials, adding the alloy melt continuously or in 2-3 times at a uniform speed, stirring the melt continuously during feeding, stirring the melt for 5-15 minutes after each feeding, controlling the temperature at 1000-1350°C, and controlling the total feeding time to 20-90 minutes. After the feeding is completed, alloying is kept at 1000-1350°C for 10-60 minutes; The first batch of raw materials is partly titanium-containing material or partly titanium-containing material and partly carbon-containing material; The second batch of raw materials is the remaining titanium-containing material and carbon-containing material; The titanium-containing materials are potassium fluorotitanate and titanium powder. In the first batch of raw materials, the titanium content generated by potassium fluorotitanate accounts for 20% to 80% of the titanium content in the target alloy, the titanium powder content accounts for 1 to 10% of the Ti content in the target alloy, and the carbon powder content accounts for 5 to 40% of the carbon content in the target alloy; in the second batch of raw materials, the titanium content generated by potassium fluorotitanate accounts for 1% to 20% of the titanium content in the target alloy, the titanium powder content accounts for 10 to 50% of the Ti content in the target alloy, and the carbon powder content accounts for 50 to 95% of the carbon content in the target alloy; S3 slag removal: after the reaction is completed, clean the salt solution or surface oxides, and control the temperature at 800-1000℃; S4 degassing and refining, the temperature is between 800 and 1000 ° C, and the alloy melt is degassed and refined for 10 to 60 minutes using argon gas to remove slag; S5 casting and continuous casting and rolling, cleaning the slag on the surface of the melt, controlling the casting temperature at 800-1000°C, casting into ingots or rolling into wires, and the obtained aluminum-titanium-carbon grain refiner contains 2%-8wt% Ti and 0.05%-2.0wt% C.

2. The manufacturing method according to claim 1, characterized in that: Auxiliary materials are added to the first batch of raw materials and / or the second batch of raw materials. The auxiliary material is one or more of K3AlF6 or Na3AlF6, KCl or MgCl2, and the addition amount of the auxiliary material is 1-15% of the mass of the batch of raw materials.

3. The manufacturing method according to claim 1, characterized in that: The titanium-containing material is titanium powder or potassium fluorotitanate; the carbon-containing material is graphite powder or nano-carbon powder.

4. The manufacturing method according to claim 1, characterized in that: The C component of the carbon-containing material is greater than 99%, and the maximum particle size is less than 100 μm; the particle size of the titanium powder is less than or equal to 0.5 mm, and the purity is about 95%.

5. The manufacturing method according to claim 1, characterized in that: The first batch of raw materials are mixed evenly and added in powder form at a uniform speed, and the second batch of raw materials are tightly wrapped with aluminum foil or pressed into blocks of 10 to 1000 g.

6. The manufacturing method according to claim 1, characterized in that: Two batches of materials are added separately, and each batch of materials is added once or multiple times.

Citation Information

Patent Citations

  • Multifunctional PVD (physical vapor deposition) film plating machine

    CN102634764A

  • Aluminum titanium carbon intermediate alloy refinement agent and preparation technology thereof

    CN104894417A